Acculturation is associated with higher prevalence of cardiovascular disease risk-factors among Chinese immigrants in Australia: Evidence from a large population-based cohort. (29th August 2020) - Jin, Kai; Gullick, Janice; Neubeck, Lis; Koo, Fung; Ding, Ding
Abstract: Background: Acculturation is associated with increased prevalence of cardiovascular disease (CVD) risk-factors among immigrants in Western countries. Little is known about acculturation effects on CVD risks among Chinese immigrants, one of the fastest growing populations in Western countries. In this study, we aim to examine the association between acculturation and CVD risk-factors among Chinese immigrants, Australia's third-largest foreign-born group. Methods: We accessed a subsample of Chinese immigrants ( n  = 3220) within the 45-and-Up Study (2006–2009). Poisson regression model with a robust error variance examined the association between acculturation and CVD risk-factors, and prevalence ratios were reported, adjusted for socio-demographic characteristics. Indicators of acculturation included age at migration, length of Australian residence and language spoken at home. The outcomes were self-reported CVD diagnosis and six risk-factors (hypertension, diabetes, high cholesterol, smoking, overweight/obesity, physical inactivity). Results: Mean age of Chinese participants was 58.9-years (SD = 10.7) and 55.5% were women. Chinese migrating to Australia aged <18 years were significantly more likely to report diabetes (prevalence ratio = 1.71; p  < 0.01), overweight/obesity (prevalence ratio = 1.49; p  < 0.001) and ≥ 3 CVD risk-factors (prevalence ratio = 1.47; p  < 0.05) compared with those who migrated after 18-years-old. Chinese immigrants who lived in Australia for ≥ 30 years were significantly more likely to have diabetes (prevalence ratio = 1.84; p  < 0.01) and ≥ 3 CVD risk-factors (prevalence ratio = 1.84; p  < 0.01). There were no significant differences by language spoken at home. The association between indicators of acculturation and CVD risk-factors appeared to differ by sex. Conclusion: Greater acculturation was associated with adverse CVD risk-factors among Chinese immigrants in Australia.